(untitled) (Journal of Building and Road Research, 2022)
This paper presents outcomes of extensive research conducted to study the behavior of reinforced concrete (RC) beams strengthened with CFRP sheets and subjected to shear and flexural loading. A 3-dimensional Finite Element (FE) modelling was carried out using ABAQUS software program to simulate the flexural and shearing behavior of a number of RC beams strengthen with CFRP. Moreover, the results of the numerical simulation were compared with actual results of experimental physical modelling of RC beams subjected to the same loading conditions for validation purpose. Appreciable number of sets of control RC beams and CFRP strengthened RC beams for flexural and shear were investigated. All beams were rectangular in cross section. To accurately describe the behavior of these tested RC beams, different material constitutive models were used in the simulation. Concrete damaged plasticity model was used to model concrete; a linear elastic perfectly plastic model was used to model both reinforcing steel and stirrups, while a linear elastic isotropic model was used to simulate the behavior of CFRP material. Moreover, the interface between concrete and CFRP material was accounted for and was simulated using a tie perfect bond model while steel reinforcement is bonded with concrete as an embedded element in ABAQUS. A careful comparison between the results of the experimental tests and those of the numerical simulation showed that the proposed FE model is able to describe the behavior of reinforced concrete beams strengthened with CFRP in terms of crack pattern and load deflection curves to an appreciable level of accuracy. Generally, the results demonstrate that numerical approach can be used to deeply investigate the behavior of RC beams strengthened with CFRP sheets. It was also concluded that the numerical approach was able to capture significant aspects of structural behavior of the tested beams such as strain distribution in CFRP, which is often not easily captured experimentally or analytically.